2019
DOI: 10.1038/s41586-019-1483-x
|View full text |Cite
|
Sign up to set email alerts
|

Seismic velocities of CaSiO3 perovskite can explain LLSVPs in Earth’s lower mantle

Abstract: Seismology records the presence of various heterogeneities throughout the lower mantle e.g. 1,2 , however, the origins of these signals, whether thermal or chemical, remain uncertain and therefore much of the information they hold about the nature of the deep Earth is obscured. Accurate interpretation of observed velocities requires knowledge of the seismic properties of all of Earth's possible mineral components. Calcium silicate perovskite (hereafter "calcium perovskite") is believed to be the third most abu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
61
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 61 publications
5
61
4
Order By: Relevance
“…The discrepancy between our results and Thomson et al (2019) 54 resulted from the usage of different elastic and velocity data for Ca-perovskite. The calculated data used in this study are from previous ab initio molecular dynamic simulations 36 , while the Ca-perovskite data adopted in Thomson et al (2019) 54 were extrapolated from low pressure to the deep mantle conditions. Since velocities measured for Ca-perovskite 54,55 are considerably lower than computational predictions at the conditions of the uppermost lower mantle, the extrapolated data would be expectedly lower than theoretical calculations 36 under deep mantle conditions.…”
Section: Discussioncontrasting
confidence: 98%
See 3 more Smart Citations
“…The discrepancy between our results and Thomson et al (2019) 54 resulted from the usage of different elastic and velocity data for Ca-perovskite. The calculated data used in this study are from previous ab initio molecular dynamic simulations 36 , while the Ca-perovskite data adopted in Thomson et al (2019) 54 were extrapolated from low pressure to the deep mantle conditions. Since velocities measured for Ca-perovskite 54,55 are considerably lower than computational predictions at the conditions of the uppermost lower mantle, the extrapolated data would be expectedly lower than theoretical calculations 36 under deep mantle conditions.…”
Section: Discussioncontrasting
confidence: 98%
“…A recent work conducted by Thomson et al (2019) 54 suggested that subducted oceanic crust would be visible as low-seismicvelocity anomalies throughout the lower mantle when data are extrapolated to the lower-mantle conditions. The discrepancy between our results and Thomson et al (2019) 54 resulted from the usage of different elastic and velocity data for Ca-perovskite.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Exploring potential MORB compositions would require testing various specific MORB compositions and Si/Fe enrichment ratios. Recently, it has been suggested that Ca‐perovskite in MORB can play a major role in explaining LLSVP velocities (Thomson et al, ). This is an interesting scenario for HPE‐enriched piles, as aluminous Ca‐perovskite is also shown to easily incorporate HPEs (Gautron et al, ; Perry et al, ).…”
Section: Discussionmentioning
confidence: 99%